Control of mercury emissions from stationary coal combustion sources in China: Current status and recommendations. (November 2016) - Hu, Yuanan; Cheng, Hefa
Abstract: Coal burning in power plants and industrial boilers is the largest combustion source of mercury emissions in China. Together, power plants and industrial boilers emit around 250 tonnes of mercury each year, or around half of atmospheric mercury emissions from anthropogenic sources in the country. Power plants in China are generally equipped with multi-pollutant control technologies, which offer the co-benefit of mercury removal, while mercury-specific control technologies have been installed in some facilities. In contrast, most industrial boilers have only basic or no flue gas cleaning. A combination of measures, including energy conservation, coal switching and blending, reducing the mercury contents of coals through washing, combustion controls, and flue gas cleaning, can be used to reduce mercury emissions from these stationary combustion sources. More stringent emission standards for the major air pollutants from coal-fired power plants and industrial boiler, along with standards for the previously unregulated mercury, were implemented recently, which is expected to bring significant reduction in their mercury emissions through the necessary upgrades of multi-pollutant and mercury-specific control technologies. Meanwhile, strong monitoring capacity and strict enforcement are necessary to ensure that the combustion sources operate in compliance with the new emission standards and achieve significant reduction in the emissions of mercury and other air pollutants. Graphical abstract: Highlights: Power plants and industrial boilers in China emit ∼250 tonnes of Hg annually. Hg is captured primarily as co-benefit of the multi-pollutant control technologies. Flue gas cleaning is being upgraded to enhance removal of Hg and other pollutants. Newly implemented emission standards can help bring large reduction in Hg emissions. Emission monitoring and enforcement efforts can drive improvement in Hg removal. Abstract : Measures on reducing emissions of Hg from power plants and industrial boilers in China are discussed, and recommendations are made to improve the effectiveness of current efforts.